Application of Rock Magnetic Methods to Landslide Disaster Vulnerability: a Case Study (Malalak, Agam Regency) - Cindy Rara Silvia; Hamdi Rifai; - Akmam (Department of Physics – Universitas Negeri Padang UNP, 2022)
Malalak is a landslide-prone area that has an undulating hilly topography with a height of more than 850 meters above sea level. Landslide potential can be determined by the value of magnetic susceptibility Percent Frequency-Dependent Susceptibility (%). The study was conducted on slopes where landslides have occurred (A) and have not occurred (B) using the rock magnetism method to compare the potential for landslides on the slopes. Soil that has been taken and measured using a Bartington Magnetic Susceptibility Meter sensor type B (MS2B), the measured values are analyzed and interpreted to see a comparison between two different samples. The results showed that the value of low-frequency magnetic susceptibility () ranged from 447.5-698.8× with an average of 580.6×, it is estimated that the magnetic mineral is ferrimagnetic with the type of mineral Hematite (Fe2O3). The graph of the relationship between the values of lf and fd% on slope A has a value of % > 2% and a slope B of % < 2%. Slope A contains superparamagnetic grains between 10%-75% which is a mixture of fine and coarse-sized superparamagnetic grains, while slope B does not exist or contains less than 10% superparamagnetic grains. The samples with high superparamagnetic grain content were almost all fine-grained soils which caused the level of soil mineral attachment by water to decrease. So that when the rainfall is high, the soil becomes saturated and accumulates on the slip plane, causing lateral movement on the slopes and landslides to occur